1994
DOI: 10.2175/wer.66.5.8
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic treatment applications and fundamentals: substrate specificity during phase separation

Abstract: The effect of phase separation on anaerobic biodegradation was evaluated in terms of thermodynamic principles. Individual components of common wastewaters were considered, and results indicate that the response of different substrates to phase-separated anaerobic treatment is diverse. A key element is the response of soluble substrates to acidification when syntrophic relationships are eliminated and biological reactions that require syntrophic relationships are altered. The acidification of carbohydrates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(51 citation statements)
references
References 43 publications
3
44
0
4
Order By: Relevance
“…Since β-oxidation of the LCFA requires a low partial pressure of hydrogen, this therefore creates an environment unfavourable for lipid degradation near the inlet. Fox and Pohland [35] also looked for inhibition of hydrogenotrophic methanogenesis, but found that this was less sensitive to LCFA inhibition than acetoclastic methane production, which agrees with the results of other investigators [36,37]. Although the current study did not investigate LCFA inhibition, this is a recognised long-term phenomenon and the impact of of lipid-rich substrates may not be realised for a substantial period of time.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Since β-oxidation of the LCFA requires a low partial pressure of hydrogen, this therefore creates an environment unfavourable for lipid degradation near the inlet. Fox and Pohland [35] also looked for inhibition of hydrogenotrophic methanogenesis, but found that this was less sensitive to LCFA inhibition than acetoclastic methane production, which agrees with the results of other investigators [36,37]. Although the current study did not investigate LCFA inhibition, this is a recognised long-term phenomenon and the impact of of lipid-rich substrates may not be realised for a substantial period of time.…”
Section: Discussionsupporting
confidence: 90%
“…Secondly, adsorption of lipids and LCFA onto bacterial cells can interfere with the mass transport of solutes such as acetate, which then inhibits methanogenesis [33]. For a substrate not consisting solely of lipids, but also containing high quantities of readily degradable polysaccharides, the readily degradable materials provide a constant source of VFA while the more slowly degradable and less easily hydrolysed lipids may build up in the digester, as in the example cited by Fox and Pohland [35] of accumulation of fats and greases at the reactor inlet for anaerobic filters treating wastewaters containing lipids and polysaccharides. The easily-acidified substrates are degraded first, creating a high hydrogen partial pressure at the inlet.…”
Section: Discussionmentioning
confidence: 99%
“…This last type of waste is high in proteins and lipids, and is relevant as the food waste feedstock used in this study also has a high lipid content. The primary breakdown products of lipids are long-chain fatty acids (LCFA); in single-stage digestion, the presence of methanogens within the same stage makes the degradation of LCFA by beta-oxidation more energetically favourable by the uptake of acetate and hydrogen produced in the process (Fox and Pohland, 1994). Pereira et al (2005) found an association of LCFA with microbial cells, and postulated that beta-oxidation may occur while LCFA is adsorbed to cells.…”
Section: Resultsmentioning
confidence: 99%
“…Average values of pH were maintained in the range of 6.3-6.6. A pH range of 4.0-6.5 has been reported as optimal for acidogenesis in a general two-phase system (Fox and Pohland, 1994). But, Komatsu et al (1991) reported that a low pH (6.0) hindered acidogenesis because the acidic pH changed LCFAs to an insoluble non-ionized form.…”
Section: Role and Its Limitation Of The Acidogenic Cstrmentioning
confidence: 99%